2017
DOI: 10.1055/s-0037-1603583
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility and Risk of Cancer

Abstract: Male infertility is a complex and incompletely understood process that is thought to affect around 10% of the male population. Infertility is a complex interaction between genetics and environmental factors, which is increasingly being recognized as a potential marker of contemporary or future medical disease, including cancer. The best characterized association between infertility and cancer risk is that of testicular germ cell tumor, but increased risk for prostate cancer, melanoma, non-Hodgkin's lymphoma, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Approximately 7.5% of American men have undergone semen analysis at an assisted reproduction center as part of a fertility evaluation, and each year nearly 700,000 men pursue an evaluation for male-factor infertility in the United States (2,3). There is a growing body of literature demonstrating that both male and female infertility may be associated with long-term health consequences, including an elevated risk of malignancy (4)(5)(6)(7). Historically, research has focused on the overall health of the female partner during an infertility evaluation.…”
mentioning
confidence: 99%
“…Approximately 7.5% of American men have undergone semen analysis at an assisted reproduction center as part of a fertility evaluation, and each year nearly 700,000 men pursue an evaluation for male-factor infertility in the United States (2,3). There is a growing body of literature demonstrating that both male and female infertility may be associated with long-term health consequences, including an elevated risk of malignancy (4)(5)(6)(7). Historically, research has focused on the overall health of the female partner during an infertility evaluation.…”
mentioning
confidence: 99%
“…Male infertility is solely responsible for 10-30% of infertility cases and contribute to 50% of overall infertility cases (2,3). Although male infertility is not a reportable disease, the manifestations of male infertility can signify a future health concern (4)(5)(6). The growing body of literature suggests that male infertility can be a potential marker of contemporary or future medical diseases including cardiovascular metabolic and autoimmune disorders as well as mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The growing body of literature suggests that male infertility can be a potential marker of contemporary or future medical diseases including cardiovascular metabolic and autoimmune disorders as well as mortality. However, exact mechanisms behind these associations remain elusive (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…While there has been extensive focus on female infertility, according to the literature, there is a correlation between some chronic disorders and male infertility, varying from cardiometabolic, autoimmune, and oncologic disorders to increased mortality rate later in life (5)(6)(7)(8)(9). The exact underlying pathophysiology of these associations remains unclear, although it is suggested that genetic, intrauterine environment and lifestyle factors may play a role (8,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%